Jackman's wolf - Hogan, Ray (Doubleday & Co Garden City, New York, 1970)
The story of a man, who, defeated by the murder of his wife and brother and the destruction of his ranch, is forced back to life by the similar plight of a young woman and her brother
36511
Keywords: Western; Frontier and pioneer life